THE ENVIRONMENTAL CARE VALUE ACTUALIZATION THROUGH THE PROGRAM DURING THE COVID-19 PANDEMIC AS A MANIFESTATION OF ECOLOGICAL CITIZENSHIP - Arum Putri Pertiwi; Marzuki Marzuki (Sosiohumaniora, 2023)
The COVID-19 pandemic is an epidemic of infectious and deadly diseases. The inculcation of environmental care values must be in the form of knowledge, attitudes, and actions for applying ecological awareness; however, citizens’ indifference becomes a challenge in planting the importance of caring for the environment. Ecological citizenship is the skill of citizens in preventing, caring for, minimizing the environment and themselves from disease outbreaks by actualizing the values of caring for the environment. This study describes the actualization of the value of caring for the environment through the program during the COVID-19 pandemic in Gunung Mas village by using descriptive-qualitative as a type of research. Data obtained by means of interviews as primary data, three people as respondents and literature study as secondary data. The data collection technique used was structured interviews. The data analysis process in writing this article consists of data reduction, data presentation, and concluding. This study’s results are programs created by Gunung Mas residents, such as protecting the surrounding environment, spraying disinfectants, healthy living patterns, and sanctions for residents who do not comply with health protocols. The environmental care value actualization carried out by the residents of Gunung Mas, namely cleaning public places once a month, providing handwashing places in public areas, using masks, throwing trash in the trash, spraying disinfectants in every house every two weeks, washing hands before After doing something, maintaining distance, exercising twice a week, worship, and verbal warning three times and if more than three times, then a penalty will be given in the form of a fine.